NARATIVE ANALYSIS OF CAMPAIGN OF PERSIJA PLAYERS ON THE VIDEO #JAGAGBK - Aprilianti Pratiwi; Retor A.W. Kaligis; Fardihian Anshari (Profetik: Jurnal Komunikasi, 2019)
The purpose of this study is to analyze the campaign narrative delivered by Persija players on the #JagaGBK video in an effort to compile the position of Jakmania in order to maintain SUGBK. The method used in this study is qualitative analysis with narrative analysis. The theory is the Narrative Paradigm theory. The results showed that the #JagaGBK video was in accordance with the three basic concepts of the Narrative Paradigm theory: coherence, truth and good reason. Persuasive campaigns carried out are relevant to the target audience because the message was conveyed by Persija players who were very familiar with Jakmania. It takes synergy between the elements of communicators, messages, communicants and the media used to conduct persuasive campaigns. If one element does not synergize with other elements, then the campaign carried out is ineffective and far from expectations. Based on the elements of the persuasive campaign, #JagaGBK video communicators are on two levels, namely the level of ideas or initiators and messengers. As the initiator of the idea was Persija management and Jakmania Chairman, while the courier was seven Persija players. The target audience for this campaign is Jakmania. The message to be conveyed is #JagaGBK. The message is packaged in videos that are spread through the Persija player's Instagram account. Through the #JagaGBK video narrative, it is expected that Jakmania can always keep GBK while watching the Persija match.